Early retirement and use of time by older Finns - Pasi Huovinen; Hannu Piekkola (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper explains early retirement using Finnish time-use data, gathered by Statistics Finland during the years 1987 and 2000. The biggest gain drawn from time-use data is the capability to give information of individuals' non-monetary activities. Finnish early retirement years are, in many ways, associated with nonpassivity. Those who are prone to active leisure and gain utility from it also have a higher probability to retire early. After verifying the importance of allocation of leisure time as an important determinant of retirement in the first stage estimations, we found interesting characteristics on leisure time by using the extension of Bordieu's division of human capital and social classes. The four main categories to build more specific time-use variables are economic capital, cultural capital, physical capital and timeintensive time use (social and passive). Active time use is also analysed separately for activities that are either typical of the educated (organised voluntary work) or uneducated (neighbourhood help). It was found that active time use consists of different activities for educated and uneducated older workers. We argue that when planning measures for longer stay in the working life it is important to take into account that (i) high-wage earners postpone retirement, (ii) the baby-boom generation has greater wealth and higher demand for early retirement schemes, (iii) men and women differ in their leisure time activities and in the determinants of early retirement. For example, sports and physical exercise is an important element, especially for women who continue to work, (iv) there is a need to raise the awareness of the vital value of voluntary work, and (v) social contacts do not explain early retirement. – – Tutkimus tarkastelee varhaiseläkkeelle siirtymistä käyttäen Tilastokeskuksen keräämää ajankäyttöaineistoa vuosilta 1987 ja 2000. Ajankäyttöaineistolla on mahdollista tarkastella vapaa-ajan kysyntää. Tutkimuksen mukaan varhaiseläkeläiset käyttävät lisääntyneen vapaa-aikansa monilla tavoin aktiiviseen toimintaan. Voidaan väittää, että työntekijät, joilla on aktiivisia vapaa-ajan harrastuksia omaavat myös suuremman todennäköisyyden poistua työmarkkinoilta. Tutkimuksen mukaan niillä ihmisillä, joilla vapaa-ajan käyttö on aktiivista, on suurempi todennäköisyys poistua työelämästä. Tutkimus tarkastelee myös Bordieun luokkateorian pohjalta inhimillisen pääoman tekijöitä, jotka vaikuttavat työelämästä poistumiseen. Pääalueita ovat taloudellinen pääoma, kulttuuripääoma, fyysinen pääoma ja aikaintensiivinen ajankäyttö (kuten sosiaalinen pääoma). Aktiivisessa ajankäytössä on myös tarpeen erottaa koulutettujen aktiivinen vapaa-ajan käyttö (organisoitu vapaaehtoistyö merkittävää) vain peruskoulutuksen saaneiden ajan-käytöstä (ns. naapuriapu keskeinen tekijä ajankäytössä). Tutkimuksen perusteella toimissa, joilla pyritään vaikuttamaan ennenaikaiseen työelämästä poistumista, on otettava huomioon, että (i) korkeapalkkaiset poistuvat myöhemmin työelämästä, (ii) suuret ikäluokat ovat vauraampia kuin edellinen ikäryhmä, joka voi lisätä vapaa-ajan kysyntää ja työmarkkinoilta poistumista, (iii) vapaa-ajan aktiviteetit eroavat miehillä ja naisilla. Esimerkiksi etenkin naisilla ns. aktiivinen liikunta myöhentää työelämästä poistumista, (iv) vapaaehtoistyön merkitys on otettava huomioon varhaiseläkkeistä koituvien kustannusten arvioinnissa ja (v) työelämä ylläpitää sosiaalista kanssakäymistä ja siten sosiaalinen kanssakäyminen ei selitä työelämästä poistumista.
Keywords: J26; J14; J22; 330; Early retirement; Time use research; Leisure; Flexible Altersgrenze; Zeitbudgetforschung; Freizeit; Alte Menschen; Finnland